Short-term evolution of edaphic parameters of mountain pastures after temporary night camping of sheep and goats - Maestro-Requena M.G.; Fernández González R.A.; Mercé Arévalo G.; Miguel-Pérez V.; Bermúdez Martínez D.; Barbas Dorado R.; Serrano Martínez E.; Busqué Marcos J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Pastoral mountain commons in the north of Spain are experiencing acute shrub encroachment and soil degradation. Livestock temporary night camping (TNC) is a traditional tool to concentrate fertility, generate high value grassland patches and ameliorate livestock grazing distribution. In this work we quantify the short-term effects of sheep TNC or goats TNC on soil fertility changes. Soil samples were collected 1 day before and 1 day, 2, 4 and 6 weeks after the establishment of 10 different TNC. Sheep and goat faeces were also collected after each TNC. Faeces and soil parameters measured were : pH, electrical conductivity –EC–, nitrogen, phosphorus and potassium. For faeces parameters, analyses of covariance were performed with time as covariable and livestock species as fixed effect. Each soil parameter was analyzed using mixed linear models, considering as fixed effects the livestock species, the value just before the TNC, and time. In faeces all parameters did not change with time but inter-specific differences were found, except for pH and organic matter. In all soil parameters, except EC, the value before TNC affected later values. Time was only significant for nitrogen (decrease), nitrate and EC (increase) ; no Time x Species interactions were found. Nitrogen in soil was higher for sheep TNC than for goats TNC, while the opposite trend was found for potassium, phospohrus and EC. Results are discussed with relation to the different grazing diets of sheep and goats and the characteristics of these podsolic soils.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)